Faktor-Faktor Yang Mempengaruhi Keputusan Audit: Good Corporate Governance, Etika Profesi Dan Kecerdasan Emosional - Reina Reina; Cris Kuntadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to determine the influence of good corporate governance, professional ethics and emotional intelligence on audit decisions. This article reviews the factors that influence audit decisions, namely good corporate governance, professional ethics, and emotional intelligence, a study of sharia accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Good corporate governance influences audit decisions, 2) Professional ethics influences audit decisions, and 3) Emotional intelligence influences audit decisions